Promoting green building in Israel: A game theory-based analysis. (October 2019) - Cohen, Chen; Pearlmutter, David; Schwartz, Moshe
Abstract: While buildings certified "green" are increasingly frequent in developed countries, they remain relatively uncommon in Israel, even though its basic green standards are undemanding. Green standards include lists of environmental benefits the buildings are providing and on rating systems assessing their relative importance and the extent of their provision. We use game theory to analyze obstacles standing in the way of the expansion and upgrading of green building in Israel and suggest steps which might help to overcome those obstacles. This paper presents five major players in the field of green building and defines their strategic options. Next, we show that the expansion of certified green building is bound to occur, as the country's foremost municipalities made such certification mandatory for all new buildings from 2017 on. However, we also show that the quality of standard implementation might even decline. Given those circumstances we consider which mix of strategies targeted towards each of those players may yield a substantial improvement in green building. We recommend expanding the use of a higher-level standard, and suggest that in order to motivate its adoption, the government should reward its builders and buyers, thus subsidizing it for a few years. The government should also ensure that the Standards Institution maintain its monopoly in certifying higher level standard implementation. Another recommended step is intensifying environmental education, and generate wider awareness of the importance of green building. Highlights: A game theory based approach for analyzing the current situation of green building in Israel is presented. The presented analysis shows that in order to encourage high quality green building in Israel, a policy reform is needed. As a result of the presented study, 3 actions are suggested for the promotion and improvement of green building in Israel: Government commitment to provide subsidies for high quality green building for a few years, until it becomes more widespread. Maintaining the monopoly of the Standards Institute over green building over two-stars or higher quality levels. Education regarding the environmental benefits and importance of green building, particularly directed towards the well-to-do.